Uji Fitokimia dan Penentuan Nilai Sun Protection Factor (SPF) Ekstrak Etanol Daun Waru (Hibiscus tiliaceus) - Dwi Fitri Yani; Rahma Hidayani; Weni Febriani; Selvira Aurelia; Doni Putra Pratama (Department of Chemistry - Universitas Bangka Belitung, 2023)
Waru leaves (Hibiscus tiliaceus) is one part of the plant that contains many secondary metabolites. One of them which have photoprotector properties that can absorbs UV rays and antioxidant properties. This study aims to determine the value of sun protection factor (SPF) using extracts ethanol. Waru leaves are extracted using 96% ethanol solvent which is then concentrated using a rotary evaporator at 40°C to evaporate the ethanol solvent. The ethanol extract contains alkaloids, tannins, flavonoids, saponins, and terpenoids. The activity of the ethanol extract of waru leaves was measured for its absorbance using a UV-Vis instrument. The highest SPF value is found in the ultra protective concentration of 1000 ppm with an SPF value of 42,29. The SPF value of the ethanol extract produced at absorbances of 200 ppm, 400 ppm, 600 ppm, 800 ppm, and 1000 ppm respectively were 4,09; 8,17; 12,48; 17,31; dan 42,29. The ethanol extract of waru leaves can protect as a sunscreen in the concentration range 200 ppm to 1000 ppm.